1997
DOI: 10.1111/j.2042-7158.1997.tb06779.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selective β-Adrenoceptor Antagonists on Gastric Ulceration in the Rat

Abstract: Metoprolol and butoxamine, beta-adrenoceptor antagonists which act selectively at the beta 1- and beta 2-adrenoceptors, respectively, have been investigated for their actions on the ethanol, indomethacin and cold-restraint stress ulcer models. Oral administration of butoxamine but not metoprolol significantly attenuated gastric mucosal damage in the three types of ulcer model. Intraperitoneal injection of butoxamine reduced indomethacin ulceration but not that of the other two models. The stimulatory effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Therefore, one should consider that the drugs used in the present study could alter the secretory activity of parietal cells and thereby preserved the decrease of PD induced by ethanol across the gastric mucosa. However, this possibility was unlikely because our previous study reported that using the same doses of the ß-adrenoceptor antagonists did not affect the secretory activity of both acid and pepsin from the stomach [5]. We therefore conclude that the respective preventive action of propranolol, nadolol and butoxamine but not metoprolol and labetalol on gastric transmucosal PD change after ethanol treatment (tables 2-4) is probably due to the protection on the gastric epithelial and glandular cells.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Therefore, one should consider that the drugs used in the present study could alter the secretory activity of parietal cells and thereby preserved the decrease of PD induced by ethanol across the gastric mucosa. However, this possibility was unlikely because our previous study reported that using the same doses of the ß-adrenoceptor antagonists did not affect the secretory activity of both acid and pepsin from the stomach [5]. We therefore conclude that the respective preventive action of propranolol, nadolol and butoxamine but not metoprolol and labetalol on gastric transmucosal PD change after ethanol treatment (tables 2-4) is probably due to the protection on the gastric epithelial and glandular cells.…”
Section: Discussionmentioning
confidence: 73%
“…In anaesthetized animals, transmucosal PD was increased after treatment with ß-adrenoceptor antagonists [4,5]. This elevation of PD was found to be important in the antiulcer action of these drugs in different types of ulceration.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The respective doses of l-ephedrine at 15 mg/kg [4], phentolamine at 1 mg/kg [7], propranolol at 1 mg/kg [8], atenolol at 5 mg/kg [8] and butoxamine at 20 mg/kg [9] were used according to or in due consideration of the references and were administered singly or in combination. Reserpine at 1 mg/kg/time was intraperitoneally administered every other day, totally 5 times [10] and the animal was challenged with the antigen on the day 5 after the last administration.…”
Section: Drug Treatmentmentioning
confidence: 99%